Tingkat Kecemasan Pada Remaja Putri Dan Mahasiswa Pada Saat Pandemi Covid- 19: Tingkat Kecemasan Pada Remaja Putri Dan Mahasiswa Pada Saat Pandemi Covid- 19 - Setiadi Syarli (Akper Kesdam I/Bukit Barisan Padang, 2021)
The coronavirus affects peoples' lives around the world. Social restriction policy can affect the psychosocial environment. Adolescents have an unstable age, so they are easily shaken psychologically, experience excessive anxiety and fear of contracting the virus. Anxiety in adolescents is a natural reaction in this time of the COVID-19 pandemic. However, if it drags on, it can cause psychological problems. Students are also prone to experiencing psychosocial problems. Psychological stressors cause changes in a person's life so that they are forced to adapt or cope with the stressors that arise. The Corona or Covid-19 virus has greatly affected life around the world. The COVID-19 pandemic outbreak threatens not only physical health, but also people's psychological health. The psychological effects can be mild to severe. Psychological impacts during a pandemic include post-traumatic stress disorder, confusion, anxiety, frustration, fear of infection, insomnia and feeling helpless. Anxiety during a pandemic can occur in a person due to predisposing factors / predisposing factors including due to the pandemic. COVID-19, spending> 9 hours at home, excessive search for information online, more common in women, economy, having babies, married status, student status, learning environment from internet networks. Some actions that can reduce anxiety are classified as reinforcing factors, namely emotional regulation, resilience, supportive intervention, religious coping, family support, limiting exposure to information media and physical activity or sports. This study aims: to determine the anxiety of young women and students during the Covid-19 pandemic. As a suggestion, some efforts can be made such as sports or physical activity, adequate rest, doing hobbies, virtual socialization and implementing a healthy environment both physically and psychologically to reduce stress and anxiety.